Kelayakan Peningkatan Tarif Retribusi di Daya Tarik Wisata Taman Sari Water Castle Kota Yogyakarta: Kajian Kelayakan Biaya - Rusmaningati, Desy; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p08, 2020)
Tamansari Water Castle is a sub-tourist attraction located in the Keraton Yogyakarta complex, this tourist attraction is famous for its heritage buildings and also for its water palace. Since it was opened to tourists on April 1, 1974 many tourists visited this tourist attraction, both domestic and foreign tourists. Since the opening of this tourist attraction for the first time, which has not yet drawn retribution rates to tourists, there have been several times the rate of retribution increases to enter this tourist attraction. So there needs to be research on the feasibility of increasing the levy rate. In this regard, the author tries to examine the "Studi Kelayakan Peningkatan Tarif Retribusi di Daya Tarik Wisata Tamansari Water Castle".                        The research method used in this study is quantitative research with comparative matrix analysis techniques, to analyze the feasibility of increasing levy rates in the tourist attraction of Tamansari Water Castle. Sources of data from primary and secondary data, data collection techniques using observation, interviews and literature studies, and interview instruments in the form of interview guidelines. Determination of informants at Tamansari Water Castle in this study using purposive sampling technique, so as to obtain accurate data about the feasibility of increasing levy rates in the tourist attraction of Tamansari Water Castle.                  The results of the research obtained were the feasibility of increasing the levy rate in the tourist attraction of Tamansari Water Castle.   Keywords: feasibility, tamansari water castle,